Diferencias estatales y regionales en el empleo rural femenino en México - Garay Villegas, Sagrario (El Colegio de México A.C., 2012)
The main purpose of this article is to present a state and regional analysis of female rural employment in Mexico, with particular emphasis on the farm and off-farm employment of women in these contexts. A conglomerate analysis is conducted, using the National Employment Survey 2003 as the main source. The main findings are as follows: the most backward regions in socio-economic terms display high rates of women’s economic participation in unsalaried secondary and tertiary activities. The regions with the greatest economic development concentrate economically active rural women in salaried jobs. The article also highlights the fact that in a region in the center of Mexico, a high proportion of women acknowledge their participation as unpaid family workers.